A meta-analysis of randomized clinical trials on the effect of metformin vs. pioglitazone monotherapy on plasma adiponectin levels among patients with diabetes mellitus - Roselle Arbas; Sofia Alexis Dayrit; Arah Dimalanta; John Ashley Flores; Arch Raphael Mañalac; Dinah Rose Soriano; Johana Vallo; Raphael Enrique Tiongco; Maria Ruth Pineda-Cortel (SpringerOpen, 2024)
Abstract Background Limited and contradicting findings were observed on the effects of both metformin (MET) and pioglitazone (PIO) on adiponectin (ADP) levels. Hence, we performed a meta-analysis of randomized control trials to obtain more precise estimates. Studies were searched, screened, and identified through different database sites. Data from included studies were extracted, pooled, and analyzed. Mean and standardized mean differences were computed with their corresponding confidence intervals. Results Overall, five studies were included in the meta-analysis. Pooled outcomes suggest that patients with diabetes receiving PIO treatment have significantly increased ADP levels. On the other hand, no significant differences were observed for those treated with MET. Other diabetes-related parameters were tested, comparing the effect of MET vs. PIO treatment, and yielded significant results for HOMA-IR and BMI. Conclusion Our study suggests that PIO significantly affects ADP levels compared to MET among patients with diabetes mellitus. However, further studies are needed to verify these claims.